International migration policy: from theories to implementations - Tetiana Dluhopolska (Вісник Харківського національного університету імені В.Н. Каразіна: Серія Міжнародні відносини, економіка, країнознавство, туризм, 2020)
The international migration policy under the conditions of migration crisis and COVID-19 pandemic is being updated both at the global level and level of national economies. Numerous international legal acts implemented by the world community since the early 1950s are further evidence that the problem of international migration is not a new, but an urgent problem that is exacerbated in the XXI century. The subject of the article is the world migration policy under the influence of the COVID-19 pandemic. The goal is to analyze the tools for regulating migration flows at the international level. Objectives: analysis of the international experience of migration policy and classification the main types of migration based on various grounds, systematization the key institutional practices of international migration regulation, assessment of the impact of the COVID-19 pandemic on international migration policy, formation the recommendations for integration of migrants into host communities of different countries. General scientific methods are used: system analysis – to determine the characteristics of global migration flows, induction and deduction – to systematize the key causes, consequences and types of international migration. The following results were obtained: current trends in global migration during 1999-2019 were analyzed, the regulatory support of migration processes at the global level was assessed, changes in remittances of migrant workers were analyzed, and the impact of the COVID-19 pandemic on international migration policy was analyzed. Conclusions: over the last 20 years, the number of international migrants has increased significantly to 271.6 million people, which is 3.5% of the world’s population; the share of migrants in the total population is highest in the UAE, Qatar, Kuwait; the most popular countries for labor migration at the beginning of 2020 are the United States, Germany and Saudi Arabia; requirements for migration policy in the XXI century are growing constantly, because of the fact that it allows to use the positive potential of migration in the interests of countries development, active international cooperation in this area, and the new challenges facing the world economy; the international migration policy is being transformed in response to the COVID-19 pandemic – many countries granting migrants a regulated status, extending their residence and work permits, providing them with access to basic health care and social security, et.